ENTREPRENEURIAL FORESIGHT AND RESPONSIBLE GROWTH IN MSMEs: LINKING OPPORTUNITY SENSING, GOVERNANCE, AND ADAPTIVE LEARNING - Arif Budi Raharja; Nazhira Nindya Padma Hanuun (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual paper develops an integrative framework for entrepreneurial foresight and responsible growth in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how financial information quality, cash-flow visibility, digital controls, liquidity discipline, and adaptive decision making can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle.